Validation of Fourier decomposition MRI with dynamic contrast-enhanced MRI using visual and automated scoring of pulmonary perfusion in young cystic fibrosis patients - Bauman, Grzegorz; Puderbach, Michael; Heimann, Tobias; Kopp-Schneider, Annette; Fritzsching, Eva; Mall, Marcus A.; Eichinger, Monika (European journal of radiology, 2013)
Purpose - To validate Fourier decomposition (FD) magnetic resonance (MR) imaging in cystic fibrosis (CF) patients with dynamic contrast-enhanced (DCE) MR imaging. - Materials and methods - Thirty-four CF patients (median age 4.08 years; range 0.16-30) were examined on a 1.5-T MR imager. For FD MR imaging, sets of lung images were acquired using an untriggered two-dimensional balanced steady-state free precession sequence. Perfusion-weighted images were obtained after correction of the breathing displacement and Fourier analysis of the cardiac frequency from the time-resolved data sets. DCE data sets were acquired with a three-dimensional gradient echo sequence. The FD and DCE images were visually assessed for perfusion defects by two readers independently (R1, R2) using a field based scoring system (0-12). Software was used for perfusion impairment evaluation (R3) of segmented lung images using an automated threshold. Both imaging and evaluation methods were compared for agreement and tested for concordance between FD and DCE imaging. - Results - Good or acceptable intra-reader agreement was found between FD and DCE for visual and automated scoring: R1 upper and lower limits of agreement (ULA, LLA): 2.72, −2.5; R2: ULA, LLA: ±2.5; R3: ULA: 1.5, LLA: −2. A high concordance was found between visual and automated scoring (FD: 70-80%, DCE: 73-84%). - Conclusions - FD MR imaging provides equivalent diagnostic information to DCE MR imaging in CF patients. Automated assessment of regional perfusion defects using FD and DCE MR imaging is comparable to visual scoring but allows for percentage-based analysis.
Gesehen am 11.11.2020